THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND PSYCHOLOGICAL WELL-BEING AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS AT SUKODADI PUBLIC HEALTH CENTER, LAMONGAN REGENCY - Umam, Khotibul; Iswatun, Iswatun; Susanto, Joko; Wijayanti, Endah Sri (Journal of Vocational Nursing, 2025)
Introduction: Type 2 diabetes mellitus is a chronic disease that commonly affects many individuals. It can lead to a lack of self-acceptance, depression, and high levels of anxiety. This can negatively impact a person's psychological well-being, making family support crucial. This study aims to analyze the relationship between family support and psychological well-being among patients with type 2 diabetes mellitus at Sukodadi Public Health Center, Lamongan Regency. Methods: This research used a quantitative correlational design with a cross-sectional study approach. The sample consisted of 50 subjects selected through consecutive sampling. The research instruments used were Hensarling's Diabetes Family Support Scale (HDFSS) and Ryff's Psychological Well-Being Scale (RPWB). Results: The results showed that almost all respondents had high family support, with 88% of respondents reporting this. More than half of the respondents demonstrated good psychological well-being, accounting for 52%. Based on the Chi-Square test, highly significant results were obtained, as evidenced by the Asymp. Sig value of P = 0.000. Conclusions: There was a significant relationship between family support and psychological well-being among patients with type 2 diabetes mellitus at Sukodadi Public Health Center, Lamongan Regency. The results of this study are expected to provide information, serve as a guideline, and offer input regarding the importance of psychological well-being, which can positively influence the health outcomes of patients with type 2 diabetes mellitus.